WORLDVIEW OF A PERSON AND HIS MENTAL THINKING IN THE WORKS OF EASTERN SCHOLARS - O. Rakhmonova (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, information is provided about the establishment of education and upbringing, which is organized in a consistent, systematic, continuous and purposeful way, and active participation in the process of social relations.